Imperialisme Gaya Baru Terhadap Buruh Industri Garmen di Bangladesh dalam Kerangka Modern World System - Sukma Ayu Putri (Journal of Governance Innovation, 2021)
Exploitation of labour has been big problems in Bangladesh, its combination between imperialist (thats the US and European Garment Consortium), local factory owners and government. Dependence Bangladesh as a periphery country under fashion companies from core country is the evidence of existing modern world system. This paper discusses about how exploitation and poverty correlate with development failures in Bangladesh. Actually, working in the garment industry are the another way to reach their basic needs, but in fact, they all getting low salary which is under minimum cost of living. Until now, the ready-made garments (RMG) industry of Bangladesh still being "big power" endorser for low skills populations within considerable polemics. Bangladesh “terperangkap” dalam skema eksploitasi tenaga kerja dari kombinasi praktek Imperialis pengusaha fashion dunia (Konsorsium Garmen AS dan Eropa) dengan pemilik pabrik dan penguasa. Ketergantungan Bangladesh sebagai negara periphery pada pengusaha fashion sebagai pemain dari negara core merupakan bentuk dari adanya modern world system yang berlaku. Tulisan ini membahas bagaimana eksploitasi, kemiskinan dan kesenjangan berkorelasi dengan gagalnya upaya-upaya pembangunan di Bangladesh. Bekerja pada industri garmen adalah pilihan terakhir para pekerja untuk memenuhi kebutuhan hidup meskipun pada kenyataannya upah yang diterima masih dibawah biaya hidup minimal yang ditetapkan. Industri garmen Bangladesh adalah “kekuatan besar” penopang ekonomi penduduk berkeahlian rendah (low-skill)  yang didalamnya mempunyai segudang polemik.